2017
DOI: 10.1177/1541931213601791
|View full text |Cite
|
Sign up to set email alerts
|

Online Education: The How, Who, Where, and When

Abstract: Undergraduate students completed an online tutorial to investigate the impact of the method of presentation on performance, the relationship between personality characteristics and performance, and where and when students complete the tutorial. Performance on the posttest was not significantly different whether students reviewed the animated video or recorded PowerPoint presentation, but performance improved in both conditions from the pretest scores. Contrary to expectation, personality was not related to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…The students using the PPT tutorial did not see the elaborative interrogation items until manually moving through the PPT slides. This result also does not corroborate Stone's (2017) finding that students responding completely online performed best using the PPT presentation. More research is needed to better understand the benefits of video and PPT presentations for different types of course content.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…The students using the PPT tutorial did not see the elaborative interrogation items until manually moving through the PPT slides. This result also does not corroborate Stone's (2017) finding that students responding completely online performed best using the PPT presentation. More research is needed to better understand the benefits of video and PPT presentations for different types of course content.…”
Section: Discussioncontrasting
confidence: 90%
“…Learning materials. A lecture on how to validate employment selection tests based on the Uniform Guidelines on Employee Selection Procedures (Equal Employment Opportunity Commission, Civil Service Commission, Department of Labor, & Department of Justice, 1978) was created by Stone (2017). Using PowerPoint (PPT), the lesson included bulleted points, as well as text boxes and graphics (e.g., arrows).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The actual space in which an online student works might also impact performance. When students completed a research study online, Stone (2017) found that just over 55% of the students reported being in a dorm room or the residence hall, with the next most frequent response being a house (18%). The specific room indicated by over 80% of the students was either their bedroom or living room.…”
Section: Online Learning Environmentmentioning
confidence: 99%